Innovation in Fiqh Learning through the Implementation of the Al-Qawaid Fiqhiyyah - Luthfah, Alfayta; Makhzuniyah, Minhah; Romlah, Siti; Yusuf, Achmad (Al-Mudarris, 2024)
This study aims to describe the innovation of Fiqh learning through the implementation of the Al-Qawaid Fiqhiyyah method for Salafiyah 2 santri in carrying out worship according to Islamic law. This research uses a descriptive method with a qualitative approach. Data collection techniques with interviews with Al-Qawaid Al-Fiqhiyyah teachers, pesantren administrators and some students. In addition, researchers obtained supporting data from observation and documentation. The results found in this study are that the implementation of Al-Qawaid Fiqhiyyah is very important in the process of student development. Because every human activity needs rules that must be applied in accordance with the Al-Quran, Hadith as well as Ulama ‘Opinions. The efforts of the Salafiyah Female Islamic Boarding School in developing Santri worship according to Islamic law by providing provision both in terms of theory and practice. In addition, the advice from the teacher can strengthen them in the development of practicing Al-Qawaid Al-Fiqhiyyah in reality. In the process of character building, there are supporting factors, namely the family and the surrounding environment that contribute to the application. Whereas families who are indifferent and leave everything to the Islamic Boarding School and the environment and friends who are not good become an inhibiting factor in the process of forming students according to Islamic Sharia.